Firm leadership and innovative performance: evidence from seven EU Countries - Kornelius Kraft; Dirk Czarnitzki (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2001)
This paper considers the effect of different firm leadership on the innovative performance of firms from seven EU countries. We investigate whether owner-led or manager-led firms achieve a larger share of their turnover with product innovations. Economic theory does not propose clear answers to this question. In the empirical analysis, it turns out that the manager-led firms are more active innovators : the share of sales based on new products is larger if firms' managers do not hold any of the firms' capital. Surprisingly, there are no differences between the seven countries included in the regression analysis.
Keywords: O31; D21; C24; O32; 330; R&D; Product Innovations; Manager; Tobit; Fractional Response Model; Innovation; Industrielle Forschung; Umsatz; Corporate Governance; Eigentümerstruktur; Schätzung; EU-Staaten